2021
DOI: 10.3390/cimb43020050
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Mining, Modification, and Application of Cellulases in Bioactive Substance Extraction

Abstract: Cellulases have been used to extract bioactive ingredients from medical plants; however, the poor enzymatic properties of current cellulases significantly limit their application. Two strategies are expected to address this concern: (1) new cellulase gene mining strategies have been promoted, optimized, and integrated, thanks to the improvement of gene sequencing, genomic data, and algorithm optimization, and (2) known cellulases are being modified, thanks to the development of protein engineering, crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…These findings indicated that the enzyme extracted from endophytic plant X-25 could significantly improve the yield of bioethanol. The superior chimerism between plant cell walls and endophytic cellulases significantly contributes to the formation of the cellulose reticular skeleton (Payne et al 2015;Hu et al 2021b). The mechanism underlying ethanol production by cellulase activity is as follows: the increased cellulase activity promotes the cleavage efficiency of the β1-4 glycosidic bond, increasing ethanol production.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that the enzyme extracted from endophytic plant X-25 could significantly improve the yield of bioethanol. The superior chimerism between plant cell walls and endophytic cellulases significantly contributes to the formation of the cellulose reticular skeleton (Payne et al 2015;Hu et al 2021b). The mechanism underlying ethanol production by cellulase activity is as follows: the increased cellulase activity promotes the cleavage efficiency of the β1-4 glycosidic bond, increasing ethanol production.…”
Section: Discussionmentioning
confidence: 99%
“…Structural comparison revealed that thermophilic and hyperthermophilic enzymes are more rigid than mesophilic enzymes. Since high temperatures unfold the highly flexible regions of the proteins quickly, flexibility can be used as an indicator to identify potential areas for modification to improve the thermal stability of BGLs [ 104 ]. Most of the current studies target mutations in flexible regions to increase protein rigidity and thermal stability.…”
Section: Engineering Of Bgl Functionalitiesmentioning
confidence: 99%
“…One strategy is to enhance the stability of the enzyme by reducing the conformational entropy in the unfolded state [ 100 ], and common methods include introducing disulfide bonds in the flexible region or replacing glycine with the most rigid proline. It has been proposed that truncating the flexible loops of the protein can also reduce the conformational entropy of BGL [ 104 ]. Another strategy is to stabilize the folded state by increasing favorable interactions (including hydrophobic interactions and hydrogen bonds, etc.)…”
Section: Engineering Of Bgl Functionalitiesmentioning
confidence: 99%
“…Structural comparison revealed that thermophilic and hyperthermophilic enzymes are more rigid than mesophilic enzymes. Since high temperatures unfold the highly flexible regions of the proteins at the first, flexibility can be used as an indicator to identify potential areas for modification to improve the thermal stability of BGLs [102]. Most of the current studies target mutations in flexible regions to increase protein rigidity and thermal stability.…”
Section: Improving Thermostabilitymentioning
confidence: 99%
“…One strategy is to enhance the stability of the enzyme by reducing the conformational entropy in the unfolded state [98], and common methods include introducing disulfide bonds in the flexible region or replacing glycine with the most rigid proline. It has been proposed that truncating the flexible loops of the protein can also reduce the conformational entropy of BGL [102]. Another strategy is to stabilize the folded state by increasing favorable interactions (including hydrophobic interactions and hydrogen bonds, etc.)…”
Section: Improving Thermostabilitymentioning
confidence: 99%